Arylative intramolecular allylation of ketones with 1,3-enynes enabled by catalytic alkenyl-to-allyl 1,4-Rh(I) migration - Partridge, Benjamin M.; Callingham, Michael; Lewis, William; Lam, Hon Wai (Wiley-VCH Verlag, 2017)
Alkenyl-to-allyl 1,4-Rh(I) migration enables the generation of nucleophilic allylrhodium(I) species by remote C–H activation. This new mode of reactivity was employed in the diastereoselective reaction of arylboron reagents with substrates containing a 1,3-enyne tethered to a ketone, to give products containing three contiguous stereocenters. The products can be obtained in high enantioselectivities using a chiral sulfur–alkene ligand.